Spectroscopic investigation of the interaction of bovine serum albumin with a novel cardiac agent V-09. Issue 1 (2008) - Chen Chen, Changyun Changyun; Ma Ma, Meihua Meihua; Zhang Zhang, Junqi Junqi; Wang Wang, Lichen Lichen; Xiang Xiang, Bingren Bingren
Abstract : This study employs fluorescence spectroscopy to characterize the binding properties of a newly synthesized cardiac agent, V-09, on bovine serum albumin (BSA). This compound shows the highest cardiac activity in the whole series. The binding constants K at 25°C and 37°C are obtained, the values are 7.12×10 4 l mol –1, 4.66×10 4 l mol –1, respectively. The standard enthalpy change (Δ H 0 ) and the standard entropy change (Δ S 0 ) are calculated to be –27.13 KJ mol –1 and 1.854 J mol –1 K –1, which indicated that hydrophobic forces play major role in the interaction between V-09 and BSA. The binding average distance between V-09 and BSA (2.57 nm) is obtained on the basis of the theory of Főrster energy transfer.